ANALISIS PERSEPSI WISATAWAN TERHADAP PENERAPAN KONSEP PARIWISATA RAMAH MUSLIM (PRM) DI TAMAN WISATA CIBODAS - Ramdani, Dadan (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2025)
Cibodas Tourism Park is a popular natural tourist destination in West Java with the potential to develop the Muslim-Friendly Tourism (MWT) concept, given the high number of Muslim tourists visiting. However, the destination currently lacks official MWT certification, necessitating a study to determine the level of implementation of the concept based on tourist perceptions. This study aims to analyse the implementation of MWT across four main dimensions: accessibility, communication, supporting environment, and services, and to measure their significance against the neutral category standard. The research method used was a descriptive quantitative approach, with data collected through questionnaires from 100 tourist respondents. Data were analysed using a one-sample t-test with a benchmark value of 3 (the